Pendekatan Humanis-Relegius pada Pendidikan Kristen sebagai Pembentukan Karakter Generasi Milenial - Petrus Marija; Yudhi Kawangung; Munatar Kause (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2019)
Prior to basic education with an age range of 6 or 7, and 8 or 9 years was a vulnerable period of cognitive, psychological, and emotional development. Children need education that can form good character and can reflect Christian values in their lives. The shift in the pattern of parental education as the first educational environment due to busy parents allows the lack of inculcation of character in the family environment. Schools become the foundation of hope for the formation of children's character in preparing generations in the millennial era. In the education process, indicators of success in learning methods are students enthusiastic about the lesson, happy, a change in thinking and attitudes of the learner's own will. Humans have a tendency for self-actualization because humans move forward to perfection or potential. Each individual has the creative ability to solve the problem. Religious humanist education contains two educational concepts that we want to integrate, namely humanist education and religious education. Integrating these two educational concepts with the aim of being able to build an education system that can shape the character of millennial generation through Christian Education. This type of research is an intrinsic case study (Intrinsic case study). Researchers focus on one particular object and are appointed as a case for in-depth study. so as to discover the reality behind the phenomenon. Based on the results of the analysis it is known that religious humanist education in Christian education has linear compounds, so the formation of the character of children, especially in this millennium era will be very tested when the religious humanist approach to Christian education can be actually carried out by educators and or educational institutions (Christian).